Strategies for Online-education Model for Project and Laboratory-based Assessment in Environmental Monitoring and Analysis Course - Hadibarata, Tony; Jusoh , Mohamad Noor Hazwan (Acta Pedagogia Asiana, 2023)
The global COVID-19 epidemic compelled all educational institutions, including universities, to cease academic instruction. To assure the ongoing process of teaching, learning, and assessment, several universities have transitioned from traditional face-to-face techniques to online ones. The purpose of the study was to examine the online-education experience in an Environmental Engineering course using a virtual lab and simulation software, as well as to determine the student's perception of the implementation of virtual labs and simulation software and the benefits of these tools for enhancing learning activities. To familiarize students with various areas of environmental engineering analysis, two simulated experiments were developed: water quality monitoring and adsorption spectroscopy. The virtual labs were generally well-received, as indicated by the responses to the Likert-type questions. Virtual laboratories are more acceptable for senior students than for first-year students, according to the consensus. 88% of respondents agreed with the average of twenty claims, compared with 3% who disagreed and 9% who agreed but disagreed with the statement. This illustrates that, although students believe that substituting virtual laboratories for conventional laboratories is not a complete solution, they believe that virtual laboratories can be used in conjunction with conventional methods to facilitate improved study outside of laboratory hours. Virtual and online learning in engineering labs are still relatively new; additional research is necessary before instructors can effectively utilize this delivery medium and its accompanying technologies to enhance student learning.